2021
DOI: 10.1021/acs.jpcc.0c09289
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Zero Charge and the Electrochemical Interface Structure of Cu(111) in Alkaline Solutions

Abstract: Copper (Cu) is a unique electrocatalyst, which is able to efficiently oxidize CO at very low overpotentials and reduce CO 2 to valuable fuels with reasonable Faradaic efficiencies. Yet, knowledge of its electrochemical properties at the solid/liquid interface is still scarce. Here, we present the first two-stranded correlation of the potential of zero free charge (pzfc) of Cu(111) in alkaline electrolyte at different pH values through application of nanosecond laser pulses and the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Cu as a coinage metal has been repeatedly found to dynamically restructure upon anion adsorption, 20 24 under reaction conditions (e.g., hydrogen evolution, 25 , 26 CO (2) reduction, 27 29 or CO oxidation 30 ), and even at its pzfc. 14 This gives rise to an inherently much lower stability of Cu surfaces compared to, e.g., Pt. While decorating Pt(111) with Ni(OH) 2 was found to result in well-separated, randomly distributed Ni(OH) 2 clusters, 5 , 6 it is doubtful that the Cu surface stays intact upon Ni(OH) 2 deposition due to its much lower cohesive energy (3.5 eV vs 5.84 eV for Pt).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cu as a coinage metal has been repeatedly found to dynamically restructure upon anion adsorption, 20 24 under reaction conditions (e.g., hydrogen evolution, 25 , 26 CO (2) reduction, 27 29 or CO oxidation 30 ), and even at its pzfc. 14 This gives rise to an inherently much lower stability of Cu surfaces compared to, e.g., Pt. While decorating Pt(111) with Ni(OH) 2 was found to result in well-separated, randomly distributed Ni(OH) 2 clusters, 5 , 6 it is doubtful that the Cu surface stays intact upon Ni(OH) 2 deposition due to its much lower cohesive energy (3.5 eV vs 5.84 eV for Pt).…”
Section: Resultsmentioning
confidence: 99%
“…At around 0.07–0.09 V RHE , coinciding with the onset of the OH adsorption peak, the transients change their sign to negative, as was previously shown for bare Cu(111) electrodes, which suggest that below this potential, a negative free charge resides at the surface. 14 , 35 This change of sign is generally attributed to the position of the pme and a turn-over of the water ad-layer. At the pme, water molecules at the interface distribute randomly, and there is no net dipolar contribution to the electrode potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 , 22 ] It has been shown that these electrodes are stable in certain electrolytes (including ionic liquids). [ 23 , 24 ] Nevertheless, their potential strongly depends on the particular electrolyte and is often only stable in a certain potential range. This is different from ideal non‐polarizable electrodes where the electrode potential does not change upon charging the electrode via faradaic or, capacitive contributions, or both.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] It has been shown that these electrodes are stable in certain electrolytes (including ionic liquids). [23,24] Nevertheless,t heir potential strongly depends on the particular electrolyte and is often only stable in acertain potential range.T his is different from ideal non-polarizable electrodes where the electrode potential does not change upon charging the electrode via faradaic or, capacitive contributions,o r both. [12,20] Overall, the task of finding au niversal reference electrode,especially for ILs,isvery complicated due to the unique chemical and physical properties of each system.…”
Section: Introductionmentioning
confidence: 99%